Non Conventional Energy Resources - Singh, Sobh; Ohio Library and Information Network; Safari, an O'Reilly Media Company (Pearson Education India, 2015)
With energy sustainability at the forefront of public discussion worldwide, there is a vital requirement to foster an understanding of safe alternative sources of energy such as solar and wind power. Tailored to the requirements of undergraduate students of engineering, Non-conventional Energy Resources provides a comprehensive coverage of the basic principles, working and utilization of all key renewable power sources"solar, wind, hydel, biomass, hyower and fuel cells. The book also consists of several solved and unsolved questions for thorough practice and revision.
Electronic reproduction.
Mode of access: World Wide Web.
Made available through: Safari, an O'Reilly Media Company.
Keywords: Electronic books